2018
DOI: 10.3390/universe4120144
|View full text |Cite
|
Sign up to set email alerts
|

Kappa Distributions: Statistical Physics and Thermodynamics of Space and Astrophysical Plasmas

Abstract: Kappa distributions received impetus as they provide efficient modelling of the observed particle distributions in space and astrophysical plasmas throughout the heliosphere. This paper presents (i) the connection of kappa distributions with statistical mechanics, by maximizing the associated q-entropy under the constraints of the canonical ensemble within the framework of continuous description; (ii) the derivation of q-entropy from first principles that characterize space plasmas, the additivity of energy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 130 publications
0
12
0
Order By: Relevance
“…It has been shown that the pseudo-additivity rule is equivalent to the Tsallis entropy and to the formulation of kappa distributions: First, we recall that Tsallis entropy [ 18 , 19 , 20 ]) is equivalent to the formulation of kappa distributions (e.g., [ 5 , 21 , 22 , 23 , 24 ]; see also: [ 25 , 26 , 27 ] and [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]); indeed, this entropic formulation is maximized under the constraints of canonical ensemble leading to kappa distributions [ 5 ], and vice versa, when maximized, the entropic formulation leads to the specific form of kappa distributions [ 37 , 38 ]. Then, it can be easily shown that the Tsallis entropic function obeys to the pseudo-additivity rule [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the pseudo-additivity rule is equivalent to the Tsallis entropy and to the formulation of kappa distributions: First, we recall that Tsallis entropy [ 18 , 19 , 20 ]) is equivalent to the formulation of kappa distributions (e.g., [ 5 , 21 , 22 , 23 , 24 ]; see also: [ 25 , 26 , 27 ] and [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]); indeed, this entropic formulation is maximized under the constraints of canonical ensemble leading to kappa distributions [ 5 ], and vice versa, when maximized, the entropic formulation leads to the specific form of kappa distributions [ 37 , 38 ]. Then, it can be easily shown that the Tsallis entropic function obeys to the pseudo-additivity rule [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, their evolution under nonstationary conditions, in particular in application to particle acceleration, is attributed to a Fokker-Planck description which naturally generates tails on the distribution function via momentum space diffusion. More basic theories have also been developed based on nonequilibrium statistical mechanics where they arise as stationary states far from thermal equilibrium [24][25][26][27][28]. In the asymptotic limit, nonlinear plasma theories [29][30][31] provide classical distributions of this kind.…”
Section: Introductionmentioning
confidence: 99%
“…This simplified assumption could be justified based on the fact that large deviations from Maxwellian EVDFs are not sustainable for a long time in collisionless plasmas, because micro-instabilities feeding from those deviations tend to restore the EVDFs back into a Maxwellian one. One distribution that combines both low-energy Maxwellian and high-energy non-Maxwellian features is the Kappa distribution, which has been extensively applied to collisionless space and astrophysical plasmas 78,79 . Mathematically speaking, a single population of Kappa distribution can be approximately decomposed in a sum of a a central Gaussian distribution function to fit the core and another Gaussian distribution function with large width to fit its wide tail.…”
Section: B Diagnosticsmentioning
confidence: 99%